PENGARUH PRESTASI BELAJAR, DUKUNGAN SOSIAL KELUARGA DAN TEMAN SEBAYA TERHADAP LITERASI KEUANGAN SISWA - Sukmawati, Dian (UNIVERSITAS NEGERI SURABAYA, 2016)
This study aims to analyzing the influence of the learning achievement of economics, family social support and peer simultaneously and partial toward financial literacy student in public senior high school in Dompu. This research is associative causal research with a quantitative approach. The population is students of 12th grade in public senior high school in Dompu. This study used proporsional area probability sampling with regression analysis techniques. The results showed that the learning achievement, social support of family and peers significantly affect the financial literacy of high school students of State in Dompu. The conclusion are 1) Economics achievement study has positive effect on the financial literacy of students, 2) Families Social support positive effect on the financial literacy of students, 3) peer social support positive influence on the financial literacy of students and 4) learning achievement, family support and peer simultaneously influence on the financial literacy of students of SMA in Dompu so that it can be said that these three variables are all factors that affect the financial literacy of high school students of State in Dompu